Morphometric analysis as an application tool to differentiate three local pen shells species - Idris, Mohd Hanafi; Arshad, Aziz; Bujang, Japar Sidik; Abd. Ghaffar, Mazlan; Daud, Siti Khalijah (Universiti Putra Malaysia Press, 2008)
Pen shells are generally large bivalves, triangular in shape with light yellow-brown to dark brown colour. They live with their pointed end embedded in sediment, attached by abundant fine byssal threads. Pen shells are relatively common at the sandy substrate of the seagrass beds inhabited by Enhalus acoroides, Halophila spp. and Cymodocea serulata, shallow lagoons and coral rubble areas. Specimens of Pinna bicolor Gmelin, Pinna deltodes Menke and Pinna atropurpurea Sowerby were collected from the seagrass beds of Merambong Shoal, Tanjung Adang Shoal and Merambong Island off South Western coast, of Johor, Peninsular Malaysia for morphological studies from August 2005 to June 2006. Naturally, P. deltodes is largely found on hard bottom substrate while, P. bicolor and P. atropurpurea are more associated with soft substrate. Physically, there was no significant external morphological difference between P. bicolor, P. deltodes and P. atropurpurea. The species was identified on the basis of nine internal and external characteristics of the valves. The three species were found to be morphologically different (P<0.05) on the basis of four major characteristics viz width of sulcus (WS), distance between posterior adductor muscle to posterior dorsal nacreous layer (PAMPDNL), dorsal posterior margin length (DPML) and shell width length (WL).